Paraonidae (Annelida: Polychaeta) of the Andaman Sea, Thailand. - Lovell, Lawrence L. (Phuket Marine Biological Center Special Publication, 2002)
Polychaetes collected from 17–198 m depth off Phuket Island, Thailand in the Andaman Sea, yielded 95 specimens representing nineteen taxa of Paraonidae. Six species are previously described. Three species are newly described herein, Aricidea (Aricidea) multiantennata n. sp., A. (A.) thailandica n. sp., and Levinsenia kirbyae n. sp. Seven taxa are provisional and three taxa are indeterminate. Aricidea elongata Imajima, 1973 and A. eximia Imajima, 1973 are newly synonymized with Aricidea (Acmira) catherinae Laubier, 1967 and A. neosuecica nipponica Imajima, 1973 is newly synonymized with A. (Acmira) simplex Day, 1963. Range extensions are reported for Aricidea (Aricidea) fragilis Webster, 1879, Aricidea (Acmira) assimilis Tebble, 1959, A. (A.) catherinae Laubier, 1967, A. (A.) simplex Day, 1963, and A. (Allia) hartleyi Blake, 1995. Species accounts, new descriptions, illustrations, and a key to the species are presented.
World Polychaeta Database (WPolyD)